Anterior translocation of the pulmonary confluence in the surgical treatment of truncus arteriosus. - Mohamed, G (1993)
A surgical technique is described for correction of truncus arteriosus type II, in which the confluence of the pulmonary arteries is translocated anteriorly to the divided truncal root. In this technique, the truncal root is reconstructed, and the ventricular septal defect is closed through a right ventriculotomy. The outflow tract of the right ventricle is reconstructed by using a cryopreserved aortic homograft, with the pulmonary artery confluence lying anteriorly to the aorta. This positioning may facilitate future reoperation in patients with this anomaly by obviating dissection around the truncal artery.